Pandangan Federasi Konstruksi Umum Dan Informal Serikat Buruh Sejahtera Indonesia (FKUI-SBSI) Terhadap Upah Minimum Kabupaten Pasuruan - Ahmad Syaifur Rizal (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study aims to examine the crucial role of the federation of the general, informal and informal federation of Indonesian welfare unions in the determination of minimum wage Pasuruan regency due to the establishment of many companies that absorb thousands of workers / labor without balanced with the fulfillment of the rights and welfare of workers. The amount of wage earned by the worker/laborer is deemed not to be irrelevant with the increase in the necessities of life to make the position of the worker/laborer in a poverty trap. As one of the containers of workers' aspirations, FKUI-SBSI championed the rights and interests of workers to increase the bargaining value in the determination of minimum wage. This type of research employs empirical jurisdiction and uses a statutory and conceptual research approach Primary data in this study comes from interviews with FKUI-SBSI leaders and secondary data derived from books, journals, and scientific papers. Based on the results of data analysis, the researchers concluded that the determination of minimum wage dilatarbelakangi by the emergence of extreme tilapia. The average tabulation value, the determination of inflation and the wage of the surrounding area that makes the difference between the union / worker and the employer, therefore in the determination of the minimum wage of FKUI-SBSI role. First, Representation in Pasuruan Regency wage council. Second, forming a shadow team as a comparison survey team and building communication with media and demonstrations